PENGARUH DIMENSI KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN BUS PO. USAHA MURNI - Wida Wulandari; Erni Masdupi (Program Studi Magister Manajemen, 2014)
The aim of this to study is determine the effect of service quality dimensions in the form of variable reliability, tangibles, responsiveness, assurance and certainty, as well as empathy towards customer satisfaction PO Usaha Murni. The population is bus customers and the number of samples 133 respondents with a accidentally sampling method. Type of data used is the primary and secondary data. Which collected using a questionnaire. The technique used to perform the analysis is regression analysis. The results showed that the Reliability (X1), Responsiveness (X3) and Empathy (X5) had no significant effect on customer satisfaction. While the Physical Evidence (X2) and the Security and Assurance (X4) significantly affected customer satisfaction. Keywords : Service quality dimension, costumer satisfaction.